Model Spiritualitas Seorang Pelayan Tuhan Bagi Pertumbuhan Rohani Jemaat - Hisikia Gulo (Jurnal Teologi Cultivation, 2021)
Abstract:Spirituality is very essential in the life of a believer as God created man in His image and likeness. Therefore, this article offers a concrete and practical model of spirituality that is easy to apply by a servant of God for the spiritual growth of the congregation. His nature as a spiritual man is a person who has experienced a renewed relationship with God, then the attributes of God are increasingly visible in his life. The purpose of writing this article is to explain how important it is, the prayer of worshiping Jesus; Second, Repentance with tears; and finally Read the story of the Saints (Hagios) in building the spirituality of a servant of God for the spiritual growth of believers. The method used in writing this article is a literature analyst from Philokalia's spirituality. The results of the study offer a model in building the true spirituality of God's servants in cultivating a relationship with God through a process of obedience that provides space, time and opens the heart personally as wide as possible for God the Holy Spirit to lead the life of a servant of God and the congregation to the relationship. intimate relationship with Jesus Christ. Keywords: Spirituality; Relation; Servant of God; Believers AbstrakSpritualitas merupakan hal yang sangat esensial dalam kehidupan orang beriman sebagaimana Allah menciptakan manusia menurut gambar dan rupa-Nya. Oleh sebab itu artikel ini menawarkan sebuah model spiritualitas yang bersifat konkrit dan praktis mudah di aplikasian oleh seorang pelayan Tuhan bagi pertumbuhan rohani jemaat. Sifatnya sebagaimana manusia rohani adalah orang yang sudah mengalami pembaruan relasi dengan Allah, maka sifat-sifat Allah semakin nampak dalam hidupnya. Tujuan penulisan artikel adalah memaparkan bahwa betapa pentingnya, doa puja Yesus; Kedua, Pertobatan dengan air mata; dan terakhir Membaca kisah orang-orang Kudus (Hagios) dalam membangun spiritualitas seorang pelayan Tuhan bagi pertumbuhan rohani orang percaya. Metode yang digunakan dalam penulisan artikel ini adalah analis literature dari spiritualitas Philokalia. Hasil penelitian menawarkan sebuah model didalam membangun spiritualitas sejati pelayan Tuhan dalam menumbuhkan-kembangkan relasi dengan Allah melalui sebuah proses ketaatan yang memberikan ruang, waktu dan membuka hati secara pribadi yang seluas-luasnya bagi Allah Roh Kudus agar memimpin kehidupan seorang pelayan Tuhan dan jemaat kepada relasi yang intim dengan Yesus Kristus. Kata kunci: Spiritualitas; Relasi; Pelayan Tuhan; Orang beriman